2010
DOI: 10.1111/j.1521-0391.2010.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress and Its Relationship to Gambling Urges in Individuals with Pathological Gambling

Abstract: We sought to explore a potential link between psychosocial stress exposure and pathological gambling (PG). Patients with PG displayed significantly higher scores on the daily stress inventory (DSI) than did healthy subjects. PG patients also displayed other heightened measures of stress, including the profile of mood states, the Spielberger state-trait anxiety inventory, the Hamilton rating scale for depression and the Beck depression inventory. Multiple regression analysis revealed that only the DSI impact sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 70 publications
10
38
0
Order By: Relevance
“…Indeed, the Depression Anxiety Stress Scale (DASS-21) required people to indicate their emotional distress in the past two weeks and the analyses on scores of the scale revealed that there were no significant differences between the three groups. The only significant difference between groups was related to stress -high levels of stress were observed in PGTs, in line with studies that have reported stress to be an independent predictor of gambling urges (Elman et al, 2010) and that have demonstrated the role of stress in the onset, maintenance (Coman et al, 1997;Friedland et al, 1992) and relapse of problem gambling (McCartney, 1995).…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, the Depression Anxiety Stress Scale (DASS-21) required people to indicate their emotional distress in the past two weeks and the analyses on scores of the scale revealed that there were no significant differences between the three groups. The only significant difference between groups was related to stress -high levels of stress were observed in PGTs, in line with studies that have reported stress to be an independent predictor of gambling urges (Elman et al, 2010) and that have demonstrated the role of stress in the onset, maintenance (Coman et al, 1997;Friedland et al, 1992) and relapse of problem gambling (McCartney, 1995).…”
Section: Discussionsupporting
confidence: 82%
“…This finding, although in a small sample (12 participants in each clinical group), indicates that differential changes in craving for different addictive behaviors may result from stress (here: gambling vs. alcohol use). In a self-report study (Elman et al, 2010) the only measure positively related to gambling urges in problem gamblers was a daily stress inventory, indicating a positive relation between stress and craving for gambling. Interestingly, in a recent pilot-study with a pharmacological challenge with yohimbine, significant left amygdala activation in response to yohimbine across all four PG subjects was observed, whereas this effect was not present in the five HCs, suggesting pharmacologically induced stress sensitization in the brain of pathological gamblers.…”
Section: Right On Cue? Cue-reactivity Studies In Problem Gamblingmentioning
confidence: 99%
“…Severe stress causes excessive release of dopamine in the mesolimbic pathways (Elman et al, 2010a,b) leading to consequential salience attribution, that is, aberrant conditioned learning (Mahan and Ressler, 2012). Similarly to pain and addiction that are two other conditions associated with erratic supraphysiological dopamine surges in the limbic system (Elman et al, 2011), aberrant salience in suicidality limits the behavioral repertoire and creates habit- rather than value-based rigid motivational states (Miranda et al, 2012) fixated on suicide-related content, in contravention to its devastating outcome and with diminution of mesolimbic neurons’ ability to detect signals for normal salience (social rewards) and loss of normal modulation of reinforcers’ values by non-suicidal contexts (Rangel et al, 2008).…”
Section: 6 Hierarchical and Multidimensional Addiction Model’s Utimentioning
confidence: 99%